Functional Traits 2.0: The power of the metabolome for ecology. (12th January 2022) - Walker, Tom W. N.; Alexander, Jake M.; Allard, Pierre‐Marie; Baines, Oliver; Baldy, Virginie; Bardgett, Richard D.; Capdevila, Pol; Coley, Phyllis D.; David, Bruno; Defossez, Emmanuel; Endara, María‐José; Ernst, Madeleine; et al.
Abstract: A major aim of ecology is to upscale attributes of individuals to understand processes at population, community and ecosystem scales. Such attributes are typically described using functional traits, that is, standardised characteristics that impact fitness via effects on survival, growth and/or reproduction. However, commonly used functional traits (e.g. wood density, SLA) are becoming increasingly criticised for not being truly mechanistic and for being questionable predictors of ecological processes. This Special Feature reviews and studies how the metabolome (i.e. the thousands of unique metabolites that underpin physiology) can enhance trait‐based ecology and our understanding of plant and ecosystem functioning. In this Editorial, we explore how the metabolome relates to plant functional traits, with reference to life‐history trade‐offs governing fitness between generations and plasticity shaping fitness within generations. We also identify solutions to challenges of acquiring, interpreting and contextualising metabolome data, and propose a roadmap for integrating the metabolome into ecology. We next summarise the seven studies composing the Special Feature, which use the metabolome to examine mechanisms behind plant community assembly, plant‐organismal interactions and effects of plants and soil micro‐organisms on ecosystem processes. Synthesis . We demonstrate the potential of the metabolome to improve mechanistic and predictive power in ecology by providing a high‐resolution coupling between physiology and fitness. However, applying metabolomics to ecological questions is currently limited by a lack of conceptual, technical and data frameworks, which needs to be overcome to realise the full potential of the metabolome for ecology. Abstract : We demonstrate the potential of the metabolome to improve mechanistic and predictive power in ecology by providing a high‐resolution coupling between physiology and fitness. However, applying metabolomics to ecological questions is currently limited by a lack of conceptual, technical and data frameworks, which needs to be overcome to realise the full potential of the metabolome for ecology.